Injury surveillance in community cricket: A new inning for South Africa - Benita Olivier; Oluchukwu L. Obiora; Candice MacMillan; Caroline Finch (AOSIS, 2022)
Published injury rates amongst elite and club-level youth cricketers highlight the need to implement injury risk-reducing strategies amongst the youth cricketing population. Data from sports injury surveillance systems are a prerequisite for the development and evaluation of strategies to reduce injury risk. Therefore, collecting injury surveillance data is a positive move towards reducing injuries in cricket. In South Africa, a systematic, standardised, evidence-informed injury surveillance system currently does not exist for community levels of play, namely, in cricket-playing high schools and cricket clubs. Although injury surveillance systems exist at elite levels, the obvious differences in elite versus community cricket settings mean that these systems cannot be implemented in their current form at community-level cricket. An innovative model is required to implement an injury surveillance system in community cricket. Clinical implications: This article proposes and describes a new research-practice partnership model to implement a systematic, standardised, evidence-informed injury surveillance system at cricket-playing high schools or cricket clubs within South Africa. Once this model has been employed, database systems will need to be established to allow long-term data management and sharing.